RNAi-mediated suppression of three carotenoid-cleavage dioxygenase genes, OsCCD1, 4a, and 4b, increases carotenoid content in rice. (14th August 2018) - Ko, Mi Ran; Song, Mi-Hee; Kim, Jae Kwang; Baek, Seung-A; You, Min Kyoung; Lim, Sun-Hyung; Ha, Sun-Hwa
Abstract : Knock-down of the carotenoid-cleavage dioxygenase OsCCD4a in rice enhances the content of carotenoids in leaves and seeds. Abstract: Carotenoids of staple food crops have a high nutritional value as provitamin A components in the daily diet. To increase the levels of carotenoids, inhibition of carotenoid-cleavage dioxygenases (CCDs), which degrade carotenoids, has been considered as a promising target in crop biotechnology. In this study, suppression of the OsCCD1, OsCCD4a, and OsCCD4b genes using RNAi was verified in transgenic rice plants by quantitative RT-PCR and small RNA detection. Leaf carotenoids were significantly increased overall in OsCCD4a -RNAi lines of the T1 generation, and the highest accumulation of 1.3-fold relative to non-transgenic plants was found in a line of the T2 generation. The effects on seed carotenoids were determined via cross-fertilization between β-carotene-producing transgenic rice and one of two independent homozygous lines of OsCCD1 -RNAi, OsCCD4a -RNAi, or OsCCD4b -RNAi. This showed that carotenoids were increased to a maximum of 1.4- and 1.6-fold in OsCCD1 -RNAi and OsCCD4a -RNAi, respectively, with a different preference toward α-ring and β-ring carotenoids; levels could not be established in OsCCD4b -RNAi. In addition, the contents of four carotenoids decreased when OsCCD1, OsCCD4a, and OsCCD4b were overexpressed in E. coli strains accumulating phytoene, lycopene, β-carotene, and zeaxanthin. OsCCD1 and OsCCD4a had a similar high carotenoid degrading activity, followed by OsCCD4b without substrate specificity. Overall, our results suggest that suppresing OsCCD4a activity may have potential as a tool for enhancing the carotenoid content of seed endosperms and leaves in rice.